Combinatorial Algorithms 22nd International Workshop, IWOCA 2011, Victoria, BC, Canada, July 20-22, 2011, Revised Selected Papers - Iliopoulos, Costas S.; Smyth, William F. (Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly referred post-workshop proceedings of the 22nd International Workshop on Combinatorial Algorithms, IWOCA 2011, held in Vancouver, BC, Canada, in July 2011. The 30 revised full papers presented were carefully reviewed and selected from a total of 71 submissions. A broad variety of topics in combinatorics and graph theory are addressed, such as combinatorics on words, string algorithms, codes, Venn diagrams, set partitions; Hamiltonian & Eulerian properties, graph drawing, colouring, dominating sets, spanning trees, and others.